An analysis of cryovolcano plumes on Enceladus by light scattering and polarimetry - Morello, Claudia Domenica (Kansas State University, 2024)
Enceladus, the sixth largest moon of Saturn, is known to be a geologically active icy body. Observations by NASA’s Cassini spacecraft show that Enceladus has cryovolcanoes on its south pole as well as a global subsurface ocean hidden beneath its frozen crust. Photographs from Cassini during flybys of Enceladus document Enceladus’s surface and the cryovolcano plumes. It is known that larger particles ejected from the cryovolcanoes deposit on the surface, while smaller particles escape into Saturn’s E-ring. Cassini observations of the sunlight scattered by the plume particles on the surface may provide information about the plume composition and potentially the dynamics of the ocean below. This work removes the coupling between orbital position and scattered plume intensity to use more of the Cassini intensity data than ever before and, with the Q-space method, shows that the particles are on average greater than 2 μm in radius and likely non-spherical. This work also presents Enceladus’ surface disk-averaged degree of linear polarization (DoLP). The plume intensities and surface DoLP are compared to spherical, spheroidal, cylindrical, and hexagonal water ice particles simulated by light scattering codes Amsterdam Discrete Dipole Approximation (ADDA) and T-Matrix for both single scattering and using a multiple-scattering approximation. The Pearson correlation coefficient is used to quantify the fit of each morphology to the Cassini data in the clear CLR (611 nm), GRN (569 nm), and MT2 (727 nm) wavelength filters and to refine the simulations. The intensity analysis of Enceladus’ plumes and the polarization of Enceladus’ surface imply the particles are likely non-spherical, and possibly occur in a size distribution with a large standard deviation and near a mean of 2 µm in radius.
Keywords: Enceladus; Light scattering; Polarization; Cryovolcanoes; Simulation; Ice